Recurrent contrast‐induced encephalopathy following coronary angiography. Issue 2 (February 2017) - Spina, Roberto; Simon, Neil; Markus, Romesh; Muller, David W. M.; Kathir, Krishna
Abstract : Contrast‐induced encephalopathy (CIE) is an acute and reversible neurological disturbance associated with the intra‐arterial administration of iodinated contrast medium during cardiac catheterisation. It may manifest with encephalopathy, motor and sensory disturbances; vision disturbances, including cortical blindness, ophthalmoplegia, aphasia; and seizures. Disruption of the blood–brain barrier and direct neuronal toxicity are believed to be implicated in the pathophysiology of the syndrome. Symptoms appear soon after contrast administration and resolve completely within 24–48 h. Risk factors may include hypertension, diabetes mellitus, renal impairment, the administration of large volumes of iodinated contrast, percutaneous coronary intervention or selective angiography of internal mammary grafts and previous adverse reaction to iodinated contrast. On cerebral imaging, CIE may mimic subarachnoid haemorrhage or cerebral ischaemia, but imaging may be normal. Prognosis is excellent with supportive management alone. CIE may recur, but re‐challenge with iodinated contrast without adverse effects has been documented. CIE is a diagnosis of exclusion and is an important clinical entity to consider in the differential diagnosis of stroke following cardiac catheterisation. Physicians should be aware of it and consider it prior to initiating thrombolysis.